2016
DOI: 10.1080/11263504.2016.1244118
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-environmental strategies in the genus Ononis L. (subsections Natrix and Viscosae) in Western Mediterranean

Abstract: Very similar morphologies have always been pointed out for subsections Natrix and Viscosae of the genus Ononis L. Morphological, environmental and biogeographic approaches do not show significant differences between taxa of both subsections, and only life form was pointed out as biological descriptor to explain taxonomic and ecological strategies for these taxa: Natrix is composed by perennial life forms, while Viscosae is solely represented by annual life forms. The discussion of results was conducted through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 30 publications
5
6
0
Order By: Relevance
“…A remarkable similarity for both Natrix and Viscosae subsections, morpho-environmentally revealed by Rocha et al (2018), was confirmed again in this work (now at the genetic level). At the same time, two of the species of subsection Natrix, O. natrix and O. ramosissima, and two of the subsection Viscosae, O. pubescens and O. breviflora, were shown to have an important genetic role in explaining the short genetic distance between both subsections.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…A remarkable similarity for both Natrix and Viscosae subsections, morpho-environmentally revealed by Rocha et al (2018), was confirmed again in this work (now at the genetic level). At the same time, two of the species of subsection Natrix, O. natrix and O. ramosissima, and two of the subsection Viscosae, O. pubescens and O. breviflora, were shown to have an important genetic role in explaining the short genetic distance between both subsections.…”
Section: Discussionsupporting
confidence: 83%
“…The relevant morphological similarity for the Ononis subsections analyzed here was already observed by Rocha et al (2018). Three morphological trends were suggested in this morpho-environmental approach, where taxa of subsection Natrix could be distinguished from those of subsection Viscosae without enough statistical significance (very low Fremove for the discriminant analysis).…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations